Evidence-Based Treatment of ADHD: Pharmacotherapy and Psychosocial Interventions in Current Clinical Guidelines - Madoń, Joanna; Czechowicz, Marta; Gadziński, Patryk (Journal of Education, Health and Sport, 2026)
Background. Attention-deficit/hyperactivity disorder (ADHD) is a condition that affects how a person focuses, regulates behavior, and manages impulses. As a result, individuals with ADHD often experience difficulties in everyday life, including at school, at work, and in social relationships. It is characterized by persistent attention deficit, hyperactivity, and impulsivity. Aim. This literature review evaluates current treatments for ADHD, including both medication and non-medication options, and discusses their effectiveness. Materials and Methods. This review summarizes current evidence on medication and psychosocial treatments for attention-deficit/hyperactivity disorder (ADHD). The review included original studies and reviews from the Cochrane, PubMed, and Google Scholar databases. The article selection process ended in February 2026. Results. Medicines that stimulate the brain are the best treatment for ADHD for people of all ages. Non-stimulant medications show moderate effectiveness and may be particularly useful in patients with contraindications to stimulants or comorbid conditions. Pharmacotherapy tends to produce larger effect sizes in children than in adults, although it is effective in both populations. Conclusions. The current evidence shows that a multimodal approach is the best way to treat ADHD. Stimulants are still the best type of drug for this, but doctors need to plan treatments for each patient that take into account their mental and social well-being, any other health problems, their age, and how well they can handle the medication to ensure the best possible care.